When “Face-to-Face” is No Longer an Option: Classroom Management Challenges During the Covid-19 Pandemics - Manea, Claudia-Neptina; Gări-Neguț, Oana (Educational Challenges, 2021)
The article examines the current context of teaching online or in a hybrid environment and provides recommendations pertaining to some of the classroom management techniques primary and secondary school teachers might find useful in their activities during the COVID 19 pandemics. The main aims of this article are to analyse the challenges posed by online teaching in relation to class management; to provide a toolkit for educators in relation to class management in an online teaching environment; and to better understand how the various learning styles of the students should be responded to by teachers as part of their classroom management techniques. The methodology which the current paper relies on involves both a critical analysis of classroom management techniques currently employed in traditional (i.e., face-to-face) and online education, as well as empirical methods pertaining to our own daily activities as educators (observation, questionnaires, conversation, dialogue, self-assessment of the learning outcomes, evaluation sheets). Building upon such methods, we formulate practical recommendations as to how an efficient classroom management should be handled to ensure that online teaching is performed at its best during the COVID-19 pandemics. The following results were attained as part of our research: the identification of the main challenges that the educators must deal with when managing the online class; a potential toolkit for the educators when managing their class in an online environment; a clearer understanding on how to best approach all students according to their styles of learning. The conclusions allow asserting that the educators have an essential role in adapting the online class management to the learning styles of the students and to the concrete particularities of e-learning during de COVID-19 pandemics, creating an optimum environment for the teaching and learning process.